Development of QR Code-Based Pocket Book Media on Solar System Materials to Increase The Science Literacy of Primary School Student - Priya Kusuma Bahari; Lilik Bintartik; Candra Utama (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
This study aimed to overcome challenges in learning Natural Sciences (Science) and increase the scientific literacy of Grade VI students at SDN 1 Sumbergedong, Trenggalek Regency, by developing a QR Code-based Pocket Book on the solar system material. The research method used is R&D and follows ADDIE's steps to develop valid, practical and effective learning media. Validation results from material experts, media experts, and teachers show a very high level of validity, 93.56%. In comparison, small-scale and large-scale trials show a high level of practicality with an average of 98.25%. Evaluating the effectiveness of using N-Gain resulted in a significant increase in student understanding by 80%. Thus, the QR Code-based Pocket Book is an innovative alternative that has the potential to increase elementary school students' scientific literacy, overcome media limitations, and enrich the learning experience with interactive multimedia technology. It is very suitable for use in solar system learning materials.